Effects of macroporous, strontium loaded xerogel-scaffolds on new bone formation in critical-size metaphyseal fracture defects in ovariectomized rats. (January 2016) - Ray, Seemun; Thormann, Ulrich; Sommer, Ursula; Khassawna, Thaqif El; Hundgeburth, Marvin; Henß, Anja; Rohnke, Marcus; Lips, Katrin S.; Heiss, Christian; Heinemann, Sascha; Hanke, Thomas; Dürselen, Lutz; et al.
Abstract: New bone formation was studied in a metaphyseal fracture-defect in ovariectomized rats stimulated by a plain and a strontium-enriched macroporous silica/collagen scaffold (ScB30 and ScB30Sr20) and a compact silica/collagen xerogel (B30). 45 female Sprague-Dawley rats were randomly assigned to three different treatment groups: (1) ScB30 (n=15), (2) ScB30Sr20 (n=15), and (3) B30 (n=15). 12 weeks after bilateral ovariectomy and multi-deficient diet, a 4 mm wedge-shaped fracture-defect was created at the metaphyseal area of the left femur. A 7-hole T-shaped plate at the lateral aspect of the femur stabilized the bone and the defect was filled with ScB30, ScB30Sr20 or B30 subsequently. After six weeks, histomorphometrical analysis revealed a statistically significant higher bone volume/tissue volume ratio in the ScB30Sr20 group compared to ScB30 (p=0.043) and B30 (p=0.0001) indicating an improved formation of new bone by the strontium-enriched macroporous silica/collagen scaffold. Furthermore, immunohistochemical results showed increased expression of BMP2 and OPG and a decreased RANKL expression in the ScB30Sr20 group. This was further confirmed with the gene expression analysis where an increase in prominent bone formation markers (ALP, OCN, Runx2, Col1a1 and Col10a1) was seen. No material remnants were found in the scaffold group indicating an almost complete degradation process of the biomaterials. This is confirmed by ToF-SIMS analysis that did not detect any strontium in the ScB30Sr20 group neither in the defect nor in the surrounding tissue. Taken together, this study shows the stimulating effects of strontium through increased bone formation by up regulation of osteoanabolic markers. This work also indicates the importance of material porosity, geometry and biodegradability in bone healing.